Primary unresectable locally invasive biatrial paraganglioma presenting with chest pain - Israa Laklouk, MD; Mahmoud L. Soliman, MD, PhD; Robert W. Pistey, MD; Sandra R. Cerda, MD (Human Pathology: Case Reports, 2018)
Paragangliomas, neuroendocrine tumors of neural crest origin, commonly occur in the adrenal medulla where they are called pheochromocytoma. Primary cardiac paragangliomas are uncommon whereby they arise in the left atrium and, less frequently, right atrium. We present a 43-year-old female with a cardiac paraganglioma presenting with ischemic and positional chest pains. CT scanning showed an infiltrative 15×10cm unresectable tumor with intense peripheral enhancement and central hypoattenuation located above the right atrium. The clinical impression was that of a high-grade sarcoma. Histopathological examination revealed tumor cell nests in a distinctive ‘Zellballen’ pattern with positive synaptophysin, chromogranin and GATA-3 staining confirming the diagnosis of paraganglioma. Immunohistochemical studies revealed that the tumor lacked the expression of SDHB and therefore indicating a SDHB gene mutation. The tumor was nonfunctioning, and therefore the absence of the classic adrenergic manifestations contributed to the late diagnosis of the condition. In conclusion, whereas preoperative diagnosis is challenging with nonfunctional paragangliomas, it is recommended that paragangliomas be considered in the differential diagnosis of cardiac neoplasms. Keywords: Paraganglioma, Cardiac, Neuroendocrine, Thoracic